Long‐term results of the cutting seton for high anal fistula. Issue 10 (21st May 2015) - Patton, Vicki; Chen, Chung Ming; Lubowski, David
Abstract Background No single procedure for high anal fistula delivers a high cure rate while also completely protecting sphincter function. This paper reports our long‐term results with the cutting seton for high fistulae and draws comparisons with advancement flap and ligation of intersphincteric fistula track (LIFT) procedures. Methods A retrospective study of prospectively collected data in consecutive patients undergoing treatment with cutting seton for high cryptoglandular fistulae was carried out. A strict protocol dictated tightening intervals of at least 4 weeks and no muscle division. In 59 patients (male : female = 39:20) followed‐up at mean 9.4 years (range 1.7–15.6 years) healing rates, continence (St Mark's score 0–24), patient‐perceived overall change in bowel control (−5 to +5), faecal incontinence quality of life (FIQL) and overall patient satisfaction (visual analogue score 0–10) were assessed. Results Primary and secondary healing rates were 93% and 98%. Mean continence score was 4.1, significantly worse in women than men (median 6, range 0–22 versus median 1, range 0–17; P = 0.006). Seventy‐eight per cent of patients had normal continence or minor incontinence (score 0–6), 13.5% moderate incontinence (score 7–12) and 8.5% severe incontinence (score >12). Sixty‐three per cent of patients had no change or improved patient‐perceived overall bowel control. Mean FIQL scores were high and significantly correlated with continence. Median satisfaction score was 9. Conclusion Cutting seton for high anal fistula achieved healing in 98% with good continence in the majority, particularly in males, and a high level of patient satisfaction. Multicentre prospective studies are needed to adequately compare cutting seton, flap and LIFT procedures.